Hubungan antara Self Regulated Learning dengan Flow Academic pada Siswa SMPN 1 Balongbendo - Mafiroh, Anisa Nur; Indriani, Ririn Dewanti Dian Samudra (ResearchJet Journal of Analysis and Inventions, 2024)
This research is motivated by the phenomenon of low academic flow where these students experience boredom in learning so that there are still students who do not do assignments and submit assignments. The purpose of this research is to see whether there is a relationship between self-regulated learning and the academic flow of SMPN 1 Balongbendo students. The variables are self-regulated learning as the independent variable and academic flow as the dependent variable. The population is all students of SMPN 1 Balongbendo with a total of 1,027 students. The sampling technique used was proportionate stratified random sampling. The data collection technique uses a self-regulated learning scale and a flow academic scale. The research hypothesis is that there is a positive relationship between self-regulated learning and the academic flow of SMPN 1 Balongbendo students. In analyzing the data using product moment correlation statistical techniques from Pearson using SPSS version 21 for windows. The results of this study's data analysis showed a correlation coefficient of 0.789 with a significance level of 0.000 <0.05, meaning that the hypothesis was accepted. So, it shows that there is a positive relationship between self-regulated learning and the academic flow of SMPN 1 Balongbendo students.